The shape and form of the 21st century academic library in South Africa : the case of the University of Cape Town libraries - Pietersen, Jeremiah (Library and Information Studies Centre (LISC), 2015)
This study sought to ascertain the shape and form of the 21st century academic library in South Africa, using the case of UCT Libraries. The objective was supported by sub-objectives, namely: to ascertain, via a rigorous review of literature, how far along academic libraries worldwide are with incorporating technological advances in their services; to identify the progress of UCT Libraries in establishing itself as a 21st century academic library; to ascertain how readily staff adapt to changes and new technology in the library; and, to ascertain user expectations of a modern, digital era academic library. A qualitative design with a case study approach was employed by the study. The study was supported by organizational learning theory. Themes emanating from the literature include, inter alia, open access, MOOCs, digital humanities and research data management. Further data was collected via interviews and a questionnaire survey of purposively sampled library staff. Stratified random sampling was used to extract samples from the targeted user population (UCT undergraduates, postgraduates and, academics and researchers) for surveying by means of online questionnaires. The study concludes that academic libraries, the world over, are adapting their services according to user demands and users’ use of current technology; that UCT Libraries is currently in the process of establishing itself as a 21st century academic library and that the progress and procedures currently in place to encourage new developments, holds UCT Libraries in good stead towards establishing itself as a 21st century academic library service; that the prevailing culture of organizational learning in UCT Libraries bodes well for constantly adapting to new technologies; and, that users are generally satisfied with the services they are receiving from the Library. Although the case of UCT Libraries was used in this study, in many ways this case is typical of academic libraries in other parts of South Africa as well as in other parts of the world and hence this study of the shape and form of the 21st century academic library has relevance to other academic library contexts as well.